Peculiar Strengths and Relational Attributes of SMEs in the Context of CSR - Jamali, Dima (Journal of business ethics, 2009)
The spotlight in the CSR discourse has traditionally been focused on multinational corporations (MNCs). This paper builds on a burgeoning stream of literature that has accorded recent attention to the relevance and importance of integrating small and medium enterprises (SMEs) in the CSR debate. The paper begins by an overview of the CSR literature and a synthesis of relevant evidence pertaining to the peculiarities and special relational attributes of SMEs in the context of CSR. Noting the thin theoretical grounding in the literature on offer, the paper then presents relevant CSR theoretical perspectives that could be useful in conducting further research on SMEs. In light of this framework, the paper outlines the findings of an empirical study highlighting the peculiar CSR orientations of SMEs in a developing country context in comparison to some of their MNC counterparts. The study is qualitative in nature, capitalizing on a comparative research design to highlight differences in CSR orientations between SMEs and MNCs. The findings are presented and implications are drawn regarding the peculiar relational attributes of SMEs in the context of CSR generally, and developing countries more specifically, and how this inclination can be further nurtured and leveraged.